Tidal‐breathing measurement of exhaled breath temperature (EBT) in schoolchildren. Issue 12 (6th March 2014) - Barreto, M.; Piacentini, G.; Chiossi, L.; Ruggeri, F.; Caiazzo, I.; Campisano, M.; Martella, S.; Villa, M.P.
Summary Background Non‐invasive assessment of airway inflammation is particularly useful in children. The exhaled breath temperature (EBT) may reflect inflammatory vasodilation and serve to assess respiratory symptoms and therapy with inhaled corticosteroids (ICs). Aims To compare EBT with other non‐invasive measurements in unselected schoolchildren in relation to respiratory symptoms and IC‐therapy, as well as to assess reproducibility, and potentially influencing factors. Methods In 298 Italian schoolchildren, we assessed tidal‐EBT, FENO, spirometry, skin‐prick tests, questionnaires on chronic respiratory symptoms, and medication. Subjects were divided as follows: reported wheeze, respiratory symptoms other than wheeze, and without symptoms. Results Subjects with reported wheeze (n = 30) more frequently presented atopy, respiratory symptoms, higher FENO, lower lung function than subjects with symptoms other than wheeze (n = 141) and those without symptoms (n = 127), but had a similar EBT. IC‐treated children (5 wheeze, 9 respiratory symptoms other than wheeze, 4 without chronic symptoms) had lower median (interquartile range) EBT levels than IC‐untreated children (n = 280) [EBT: 31.7 (30.1–32.5) vs. 32.6 (31.4–33.4), P = 0.027]. Duplicate EBT measurements were highly reproducible (ICC = 0.94). In a multiple linear‐regression model, EBT was explained by age, weight, duration of EBT measurement, FENO, and ambient temperature (r = 0.63, P < 0.001). Conclusion Tidal‐EBT measurements are easy to perform, reproducible, though symptom misclassification may affect the results obtained regarding the effect of IC therapy. Factors influencing EBT should be addressed in further epidemiological studies. Pediatr Pulmonol. 2014; 49:1196–1204. © 2014 Wiley Periodicals, Inc.